PRINCIPLE OF HUMANIZATION AND PSYCHOLOGIZATION OF PEDAGOGICAL MANAGEMENT AS A BASIS PERSONAL-ORIENTED IMPLEMENTATIONS TRAINING DURING THE PROFESSIONAL PROCESS TRAINING OF PEDAGOGICAL STAFF - Shtelmakh, H.B.; Polishchuk, O.B. (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the principle of humanismation and psycholigation of pedagogical management during professional training.